Editor’s Message - Verde, Linda (Operating Room Nurses Association of Canada Journal, 2026)
We are well into 2026, and it has already been an interesting year. If you are finding our global situation adds stress to your days, or nights, focusing on something completely different is a good way to give yourself a break. Our Spring Issue can let you put those worries aside while delighting in advancing your professional knowledge and best practice. So, get comfortable with your beverage of choice and fire up your device.